The Construction and Empirical Study on Evaluation Index System of International Low-Carbon Economy Development - Zhongyu, Zhang; Zhongxiang, Zhang (Frontiers in Energy Research, 2021)
Global climate change has become one of the core issues of world governance. Many countries have put forward the goal of carbon neutrality one after another, leading to the intensification of international low-carbon economy competition. In order to assess the current low-carbon competitiveness among countries, this paper constructs an evaluation index system of international low-carbon economy development, and obtains the scores and rankings of countries in energy, society, economy and environment, as well as overall. Taking 20 countries with the highest carbon emissions in the world in 2019 as samples, starting from the concept of low-carbon economy and five evaluation principles, this paper selectes 40 low-carbon evaluation indicators from five aspects, including economy, society, science and technology, environment and energy structure. By using principal component factor analysis method to calculate and test, the four factors, energy factor, society factor, economy factor and environment factor, are finally extracted to construct the evaluation index system. Results show that South Korea, France, China, Canada and Germany are among the world's top five low-carbon economies. The overall competitiveness of China's low-carbon economy is in a relatively favorable position (3rd overall), with the most outstanding performance in terms of economic strength (1st), but poor performance in terms of social development (9th) and environmental carrying capacity (9th), and the biggest disadvantage in terms of energy structure (13th).